Physiologically based pharmacokinetic modeling of daptomycin dose optimization in pediatric patients with renal impairment - Ye, Lingling; You, Xiang; Zhou, Jie; Wu, Chaohui; Ke, Meng; Wu, Wanhong; Huang, Pinfang; Lin, Cuihong (Frontiers in Pharmacology, 2022)
Background and Objective: Daptomycin is used to treat gram-positive infections in adults and children and its dosing varies among different age groups. We focused on the pharmacokinetics of daptomycin in children with renal impairment, which has not been evaluated. Methods: A physiologically based pharmacokinetic (PBPK) model of daptomycin was established and validated to simulate its disposition in healthy populations and adults with renal impairment, along with a daptomycin exposure simulated in pediatric patients with renal impairment. Results: The simulated PBPK modeling results for various regimens of intravenously administered daptomycin were consistent with observed data according to the fold error below the threshold of 2. The Cmax and AUC of daptomycin did not differ significantly between children with mild-to-moderate renal impairment and healthy children. The AUC increased by an average of 1.55-fold and 1.85-fold in severe renal impairment and end-stage renal disease, respectively. The changes were more significant in younger children and could reach a more than 2-fold change. This scenario requires more daptomycin dose adjustments. Conclusion: Dose adjustments take into account the efficacy and safety of the drug; however, the steady-state Cmin of daptomycin may be above 24.3 mg/L in a few instances. We recommend monitoring creatine phosphokinase more than once a week when using daptomycin in children with renal impairment.